2015
DOI: 10.1109/tmi.2014.2365030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound RF Time Series for Classification of Breast Lesions

Abstract: This work reports the use of ultrasound radio frequency (RF) time series analysis as a method for ultrasound-based classification of malignant breast lesions. The RF time series method is versatile and requires only a few seconds of raw ultrasound data with no need for additional instrumentation. Using the RF time series features, and a machine learning framework, we have generated malignancy maps, from the estimated cancer likelihood, for decision support in biopsy recommendation. These maps depict the likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 62 publications
0
35
0
1
Order By: Relevance
“…For example, in quantitative ultrasound imaging of cancer [42, 43], the raw ultrasound radio-frequency (RF) signals are divided into small ROIs, and each ROI is analyzed to extract spectral features for tissue characterization. Moreover, a recent study by Uniyal et al [44] has compared the classification performance of a combination of ultrasound-based texture, spectral, and RF time series features that are extracted from the entire breast tumor with the performance obtained by dividing the tumor into 1 × 1 mm 2 ROIs and extracting similar ultrasound-based features from each individual ROI. This study demonstrates that the classification performance obtained by classifying the individual 1 × 1 mm 2 ROIs outperforms the classification results achieved by classifying the entire tumor.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in quantitative ultrasound imaging of cancer [42, 43], the raw ultrasound radio-frequency (RF) signals are divided into small ROIs, and each ROI is analyzed to extract spectral features for tissue characterization. Moreover, a recent study by Uniyal et al [44] has compared the classification performance of a combination of ultrasound-based texture, spectral, and RF time series features that are extracted from the entire breast tumor with the performance obtained by dividing the tumor into 1 × 1 mm 2 ROIs and extracting similar ultrasound-based features from each individual ROI. This study demonstrates that the classification performance obtained by classifying the individual 1 × 1 mm 2 ROIs outperforms the classification results achieved by classifying the entire tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Moon et al located the region of tumor, and then classified the benign and malignant tumor with interior echo and morphological characteristic [10]. Uniyal et al utilized RF time sequence characteristics and machine learning method to generalize the estimated probability graph of tumor and then realized classification [11]. And Nayeem et al proposed a method based on sparse representation to classify tumor [12].…”
Section: Related Researchmentioning
confidence: 99%
“…It was found that the dictionary significantly assists in classification process. Uniyal et al [44] have implemented a technique that uses time-series analysis to perform classification of the malignancy in breast cancer. The technique generates a map of malignancy using machine learning approach.…”
Section: B Classification Techniquessmentioning
confidence: 99%